2011 IEEE International Conference on Systems, Man, and Cybernetics 2011
DOI: 10.1109/icsmc.2011.6084185
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation features for synthetic aperture sonar image seabed segmentation

Abstract: Abstract-High-resolution synthetic aperture sonar (SAS) systems yield richly detailed images of seabed environments. Algorithms that automatically segment and label seabed textures such as coral, sea grass, sand ripple, and mud, require suitable features that discriminate between the texture classes. Here we present a robust, parameterized SAS image texture model based on the autocorrelation function (ACF) of the intensity image. This ACF texture model has been shown to accurately model first-and second-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In the experiments from Cobb and Principe, 69 the excellent performance of wavelet coefficients in characterizing the texture information of sonar images has also been proven.…”
Section: Basic Concepts Of Waveletsmentioning
confidence: 88%
“…In the experiments from Cobb and Principe, 69 the excellent performance of wavelet coefficients in characterizing the texture information of sonar images has also been proven.…”
Section: Basic Concepts Of Waveletsmentioning
confidence: 88%
“…Unser and Coulon [38] used correlation and grey level difference measure in an automatic visual inspection system of texture. Moreover, the method has been used to extract features for synthetic aperture sonar image seabed segmentation [39].…”
Section: ) Examples Of Applicationsmentioning
confidence: 99%
“…[14] presents a sand ripple model that using sinusoid functions with different orientations and scales to characterize the sand ripple pattern as three highlightshadow pairs. [21] applies autocorrelation function to extract seabed features which perform especially well for extracting periodically patterns. However, it has been reported that autocorrelation is not a suitable measure for coarseness [22] (i.e., if a texture has bigger element sizes and fewer elements are repeated, the texture is coarser [23]).…”
Section: Related Workmentioning
confidence: 99%